How do you find the derivative of y=ln(1+e^x/1-e^x)?

2 Answers

I think that this was not the function that you intended to write (probably you omitted parentheses, which are essential when one writes in-line fractions). In fact, you can rewrite that function as follows:
c(x)=ln(1+e^x/1-e^x)=ln(1+e^x-e^x)=ln(1)=0
The derivative of a constant function is 0, so
c'(x)=0


I'll try to infer the function that you wanted to write:
f(x)=ln((1+e^x)/(1-e^x))
The code to render this properly is f(x)=ln((1+e^x)/(1-e^x)) (notice the usage of parentheses).

This is a function composition. Given two functions y=g(x) and z=h(y) you can compute the derivative of the composition f(x)=h(g(x)) as follows:
f'(x)=h'(g(x))*g'(x)
In this particular case g(x)=(1+e^x)/(1-e^x) and h(y)=ln(y).

The derivative of g we is the derivative of a quotient
g'(x)=(e^x(1-e^x)-(1+e^x)(-e^x))/(1-e^x)^2=(2e^x)/(1-e^x)^2
and the derivative of h is the derivative of the logarithmic function
h'(y)=1/y
So
f'(x)=h'(g(x)) * g'(x)=1/((1+e^x)/(1-e^x)) * (2e^x)/(1-e^x)^2=(2e^x)/((1+e^x)(1-e^x))=(2e^x)/(1-e^(2x))

Apr 26, 2015

I assume you want to differentiate:

y=ln((1+e^x)/(1-e^x)).

You could use d/dx (lnu) = 1/u (du)/dx with u = (1+e^x)/(1-e^x) and use the quotient rule to find (du)/dx, but it's a little quicker to use ln(a/b) = lna - lnb to rewrite the function as:

y=ln(1+e^x) - ln(1-e^x). before differentiating:

y' = 1/(1+e^x) e^x - 1/(1-e^x) (-e^x)

Or, simplifying:

y' = e^x/(1+e^x) + e^x/(1-e^x) = (2e^x)/(1-e^(2x))